Архетип вода в поліському мовному просторі - Сімович, О. (Волинь-Житомирщина. Історико-філологічний збірник з регіональних проблем, 2010)
У статті проаналізовано кілька аспектів функціювання одного з найпоширеніших архетипових символів вода, підкреслено зв’язок семантики символу з ритуалом. Представлений матеріал відтворює вагому частину мовної культури Полісся. In this paper the functioning of widely distributed archetype symbol (water) is discussed. It is shown that the semantic of symbol is closely associated with ritual. This material is essential for research of language culture of Polissia. In this paper the functioning of widely distributed archetype symbol (water) is discussed. It is shown that the semantic of symbol is closely associated with ritual. This material is essential for research of language culture of Polissia.